Novel lncRNA-miRNA-mRNA Competing Endogenous RNA Triple Networks Associated Programmed Cell Death in Heart Failure - Zheng, Yu; Zhang, Yingjie; Zhang, Xiu; Dang, Yini; Cheng, Yihui; Hua, Wenjie; Teng, Meiling; Wang, Shenrui; Lu, Xiao (Frontiers in Cardiovascular Medicine, 2021)
Objective Increasing evidence has uncovered the roles of lncRNA-miRNA-mRNA regulatory networks in cardiovascular diseases. However, the crosstalk between ceRNA networks and development of heart failure (HF) remains unclear. This study was to investigate the role of lncRNA-mediated ceRNA networks in the pathophysiological process of HF and its potential regulatory functions on programmed cell death. Methods We firstly screened the GSE77399, GSE52601 and GSE57338 datasets in the NCBI GEO database for screening differentially expressed lncRNAs, miRNAs and mRNAs. lncRNA-miRNA-mRNA regulatory networks based on the ceRNA theory were subsequently constructed. GO and KEGG enrichment analysis was conducted to predict potential biological functions of mRNAs in ceRNA networks. Differentially expressed mRNAs were then interacted with programmed cell death related genes. lncRNA-mediated ceRNA regulatory pathways on programmed cell death were validated with qRT-PCR testing. Results Based on our bioinformatic analysis, two lncRNAs, eight miRNAs and 65 mRNAs were extracted to construct two lncRNAs-mediated ceRNA networks in HF. Biological processes and pathways were enriched in extracellular matrix. Seven lncRNA-mediated ceRNA regulatory pathways on programmed cell death, GAS5/miR-345-5p/ADAMTS4, GAS5/miR-18b-5p/AQP3, GAS5/miR-18b-5p/SHISA3, GAS5/miR-18b-5p/C1orf105, GAS5/miR-18b-5p/PLIN2, GAS5/miR-185-5p/LPCAT3, and GAS5/miR-29b-3p/STAT3, were finally validated. Conclusions Two novel ceRNA regulatory networks in HF were discovered based on our bioinformatic analysis. Based on the interaction and validation analysis, seven lncRNA GAS5-mediated ceRNA regulatory pathways were hypothesized to impact programmed cell death including seven for apoptosis, three for ferroptosis, and one for pyroptosis. Upon which, we provided novel insights and potential research plots for bridging ceRNA regulatory networks and programmed cell death in HF.